Roycean loyalty in William Shakespeare's Timon of Athens - Toh, Florence Haw Ching; Ali Termizi, Arbaayah (Penerbit Universiti Kebangsaan Malaysia, 2012)
The study focuses on the master-servant relationship shared by the Steward and Timon in Shakespeare’s Timon of Athens (1605). The paper begins with a brief overview on the notion of loyalty and moves towards reviewing some master-servant relationships found in Shakespeare’s plays. While most studies highlight the comical nature and bearings of the servant class, the study centers its analysis on the serious nature of loyalty displayed by the Steward towards Timon. The social establishment pertaining to the practice of loyalty within the Elizabethan servant class is also presented. Following the literature review on the Steward is an account which explains Josiah Royce’s concepts of loyalty forwarded in his work The Philosophy of Loyalty (1908). The discussion of the study highlights the Steward’s loyalty in truth speaking, minimizing conflicts and idealizing the lost cause which enhances his self-will and forgoes his self-gratification. The paper concludes with an emphasis on the eminent role and nobility of the Steward in serving his master, Timon. Through the instances and extent of loyalty examined, the study aims to instigate new textual interpretations in the area of master-servant relationships within Shakespeare’s playtexts.